Setting-up schools of excellence: the role of public private partnerships in emerging economies. Issue 5 (23rd December 2014) - Sundaram, Satyam Shivam; Mishra, Pavitra
Abstract : Subject area: – Project structuring. Study level/applicability: – The case can be used for MBA, Executive MBA, Faculty Development Program (FDP) and Management Development Program (MDP) to introduce them to the selection of procurement method, concept of value for money and project structuring in the context of the education sector. Case overview: – Saryu Secondary Schools of Excellence Samiti (SSSES) functioned under the chairmanship of the Minister of Human Resource Development and was running 584 Saryu Secondary School of Excellence (SSSE) as of March 15, 2013. SSSE were focused on providing quality education to poor children, primarily from rural areas. In January 2013, SSSES was given a mandate to open 75 additional schools within one year and 500 schools within five years in rural and semirural areas to meet the demands of secondary education in India.The Managing Director of SSSES, was preparing for the meeting to be held on March 31, 2013 to discuss various options for development of the mandated schools including involvement of private player under the Private Finance Initiative (PFI) model. Expected learning outcomes: – The case introduces the participants to the challenges in the education sector including public delivery system, poor economic status of students, selection of appropriate procurement method (public delivery versus buying of service from private sector) and project structuring issues. Specific objectives are: introduce participants to the challenges of delivering education services; establish the benefit of PFI in social infrastructure domain and introduce the participants to the concept of value for money; identify risks and returns under various structures; and impress on importance of non-commercial issues which may shape a project. Supplementary materials: – Teaching Notes are available for educators only. Please contact your library to gain login details or emailsupport@emeraldinsight.com to request teaching notes.